Accounting on the block: an alternative teaching tool towards enhancing malay students performance heritage in accounting / Zuhariah Husin … [et al.] - Husin, Zuhariah; Mohd Din, Norlaila; Jamaluddin, Junaidah; Mohammad Fadzillah, Nur Syazwani; Nias Ahmad, Mohamad Azmi (2015)
Previous research has found that the use of teaching aid is beneficial to enhance students' perceptions on learning, examination performance and learning process. Accounting on the Block (AOTB) is undertaken with the objective to provide an efficient, enjoyable and game-like teaching tool in teaching the basic preparation of published financial statements as part of the financial accounting curriculum in UiTM. It is also to enhance the performance of UiTM students in important accounting topic involving the preparation of published financial statement. This tool uses magnetic blocks with printed financial statement items that can be attached to the white board. Primary data were collected before and after the application of AOTB in classes. The performance- related data collected for FAR160 is based on the score of assignment on published financial statements before the use of AOTB in class and is compared to the score of examination questions on the same topic after the application of AOTB. Students are no longer sitting in one place listening and taking notes but they have to be more interactive in completing their assignments. A trial run with Diploma in Accountancy students recorded a shorter time taken to complete a set of financial statements and they seemed to enjoy learning using this tool. The findings reveal a better score for published financial statements after the use of AOTB. It is hoped that this tool will in a way contribute to the increased passing rate of students and consequently completing the programme on time, thus enhancing the performance heritage of Malay students.